Portimine A toxin causes skin inflammation through ZAKα-dependent NLRP1 inflammasome activation - Léana Gorse; Loïc Plessis; Stephen Wearne; Margaux Paradis; Miriam Pinilla; Rae Chua; Seong Soo Lim; Elena Pelluz; Gee-Ann TOH; Raoul Mazars; Caio Bomfim; Fabienne Hervé; et al. (EMBO Molecular Medicine)
Abstract In 2020–2021, a “mysterious illness” struck Senegalese fishermen, causing severe acute dermatitis in over one thousand individuals following exposure through drift-net fishing activity. Here, by performing deep analysis of the environmental samples we reveal the presence of the marine dinoflagellate Vulcanodinium rugosum and its associated cyclic imine toxins. Specifically, we show that the toxin PortimineA, strongly enriched in environmental samples, impedes ribosome function in human keratinocytes, which subsequently activates the stress kinases ZAKα and P38 and promotes the nucleation of the human NLRP1 inflammasome, leading to the release of IL-1β/IL-18 pro-inflammatory cytokines and cell death. Furthermore, cell-based models highlight that naturally occurring mutations in the P38-targeted sites of human NLRP1 are unable to respond to PortimineA exposure. Finally, the development and use of human organotypic skins and zebrafish models of PortimineA exposure demonstrate that the ZAKα-NLRP1 axis drives skin necrosis and inflammation. Our results exemplify the threats to human health caused by emerging environmental toxins and identify ZAKα and NRLP1 as important pharmacological targets to mitigate PortimineA toxicity.